mnyʿt dryst rgl khmṭrd: lḳṿrṿtyṿ shl hmṿnḥ ׳dṿṿshʾ׳ / Prevention of Right of Ownership: The Development of the Term “Davsha” - Glicksberg, Shlomo A. (Hebrew Union College annual, 2013)
The second chapter of b. Bava Batra deals with the necessity of preventing nuisances in private houses and grounds. One of the novel ideas in this talmudic unit is that a landowner has some legal rights, though limited to specific cases, to his neighbor's land. According to the principle of “davsha,” which will be presented in this article, every landowner must leave a strip of land, four cubits wide, near his neighbor's wall upon which pedestrians can walk - thus strengthening the foundations of the wall. This law, which originates in the Babylonian discussion of m. Bava Batra 2:4, has, over the course of time, undergone many interpretive changes, from its appearance in the Mishnah, to its status in halakhic literature, to the way it is practiced today. From an interpretation of the talmudic sources we can conclude that the origin of “davsha” as a concept - and as a new type of nuisance - should be attributed to the anonymous editors of the Talmud and regarded as an interpretation rather than a regulation. The concept at the base of this term definitely broadens the definition of the nuisance laws; however, “davsha” remains only theoretical, since already in the early medieval period this law was stripped of its practical consequences.